B.P.R.D. omnibus - Mignola, Michael 1960-; Golden, Christopher 1967-; Arcudi, John (Dark Horse Books, 2022)
"In 2001 Hellboy quit the B.P.R.D., leaving its roster of special agents to defend the world from any occult threats and the growing menace of the frog army. Now their adventures are collected in one continuous saga, following the exploits of Abe Sapien, Liz Sherman, Roger the Homunculus, Johann Krauss, Kate Corrigan, Ashley Strode, and many more, from the war on frogs through the end of Ragna Rok. Join Hellboy creator Mike Mignola and a slew of talented writers and artists as they bring you the main collection of B.P.R.D. stories in a series of ten volumes"--
"From the world of Hellboy"--Cover
Keywords: Hellboy -- Fiktive Gestalt; Paranormales Erlebnis; Parapsychologie; Das Übersinnliche; Hellboy / (Fictitious character from Mignola) / Comic books, strips, etc; Supernatural / Comic books, strips, etc; Good and evil / Comic books, strips, etc; Parapsychology / Comic books, strips, etc; Fantasy comics; Graphic novels; Horror comics; Paranormal comics; Comic